Preliminary Results of Caregiver Speaks: A Storytelling Intervention for Bereaved Family Caregivers. Issue 5 (3rd July 2020) - Rolbiecki, Abigail J.; Oliver, Debra Parker; Washington, Karla; Benson, Jacquelyn J.; Jorgensen, Lucas
Abstract: When bereaved cancer caregivers have the opportunity to tell stories about their caregiving and bereavement journey, they are better able to make meaning of these experiences. Creating a space where they can share stories with other bereaved caregivers increases social validation, facilitates the meaning-making process, and reduces distress and risk for complicated grief. This study explored the feasibility and acceptability of an innovative storytelling intervention for bereaved family caregivers of cancer patients. Twenty-one participants engaged in the intervention, and eleven were interviewed about their experience. Results indicated study feasibility and intervention acceptability. Suggestions for future intervention were also provided.